Graft Preparation for Combined ACL and ALL Reconstruction With a Single Femoral Tunnel - Camilo Partezani Helito MD, PhD; Tales Mollica Guimarães MD; Marcel Faraco Sobrado MD (SAGE Publishing, 2021)
Background: Combined reconstruction of the anterolateral ligament (ALL) and anterior cruciate ligament (ACL) has shown excellent results. It could potentially reduce graft failure and improve outcomes in high-risk patients. There are several surgical techniques described. Hamstrings are the most frequently used graft for ALL reconstruction. The distal portion of the iliotibial band is used for the modified Lemaire procedure. Indications: Anterior cruciate ligament reconstructions associated with the following risk factors: pivoting sports, high-demand athletes, high-grade pivot-shift, chronic ACL injury, lateral femoral condyle notch, Segond fractures, young patients (<20 years), ACL revision, generalized hyperlaxity, and Lachman >7 mm. Technique Description: Semitendinosus and gracilis tendons are harvested and their extremities are prepared with continuous suture. The semitendinosus graft is folded in 3 parts leaving the ends of the graft internalized. The triple semitendinosus will be the main component of the ACL and the single gracilis will be used for both ACL and ALL. Anterolateral ligament anatomical landmarks are proximal and posterior to the lateral epicondyle in the femur, and in the mid distance from the fibular head and the Gerdy tubercle in the tibia. The ALL is fixed in knee extension with interference screws. This video also includes a brief demonstration of graft preparation for the modified Lemaire procedure. Results: Results from our group using this technique have shown excellent clinical outcomes, minimal complications, and low failure rates in high-risk populations. This graft preparation shows excellent diameter and length for combined ACL and ALL reconstruction. Conclusion: This technique is easy to perform, with minimal complications, and should be considered in high-risk patients undergoing ACL reconstruction.